Neuropathic pain clinical trials: factors associated with decreases in estimated drug efficacy. Issue 11 (November 2018) - Finnerup, Nanna B.; Haroutounian, Simon; Baron, Ralf; Dworkin, Robert H.; Gilron, Ian; Haanpaa, Maija; Jensen, Troels S.; Kamerman, Peter R.; McNicol, Ewan; Moore, Andrew; Raja, Srinivasa N.; Andersen, Niels T.; et al.
Abstract : Abstract: Multiple recent pharmacological clinical trials in neuropathic pain have failed to show beneficial effect of drugs with previously demonstrated efficacy, and estimates of drug efficacy seems to have decreased with accumulation of newer trials. However, this has not been systematically assessed. Here, we analyze time-dependent changes in estimated treatment effect size in pharmacological trials together with factors that may contribute to decreases in estimated effect size. This study is a secondary analysis of data from a previous published NeuPSIG systematic review and meta-analysis, updated to include studies published up till March 2017. We included double-blind, randomized, placebo-controlled trials examining the effect of drugs for which we had made strong or weak recommendations for use in neuropathic pain in the previously published review. As the primary outcome, we used an aggregated number needed to treat for 50% pain reduction (alternatively 30% pain reduction or moderate pain relief). Analyses involved 128 trials. Number needed to treat values increased from around 2 to 4 in trials published between 1982 and 1999 to much higher (less effective) values in studies published from 2010 onwards. Several factors that changed over time, such as larger study size, longer study duration, and more studies reporting 50% or 30% pain reduction, correlated with the decrease in estimated drug effect sizes. This suggests that issues related to the design, outcomes, and reporting have contributed to changes in the estimation of treatment effects. These factors are important to consider in design and interpretation of individual study data and in systematic reviews and meta-analyses. Abstract : Supplemental Digital Content is Available in the Text.In the past 35 years, altered study design methodology has contributed to decreases in estimated drug effect size from randomized controlled trials in neuropathic pain.